Protein profile analysis of scorpion (Heterometrus swammerdammi) venoms by two-dimensional gel electrophoresis - Arthiyan, S.; Jeyasutha, R.; Murugananthan, A.; Eswaramohan, T. (Faculty of Science, University of Jaffna, 2020)
Scorpions are globally known to be venomous as well as medically important creatures. They possess millions of years of evolutionary history with considerable diversity. Heterometrus swammerdammi from the family Scorpionidaeis one of the less harmful scorpions found in the Jaffna peninsula. There are no reports available about their protein profile from Sri Lanka. Therefore, the current research was undertaken to report their protein profile. The scorpions were sampled from selected locations of the Jaffna Peninsula and their venom was extracted using the electrical stimulation method immediately after the sampling. The sampled scorpions were housed in the Animal house of Department of Zoology, University of Jaffna with the supply of food and water at libitum. The Sodium Dodecyl Sulphate - Polyacrylamide gel Electrophoresis (SDS-PAGE) of Laemmli was used in the profiling of scorpion venom with the 10% polyacrylamide gel and protein marker. The Coomassie brilliant blue stain was used to stain the gel and distilled water was used to de-stain the gel and then the gel was analysed. The protein marker consists of bands sized 225, 150, 100, 75, 50, 35, and 25 kDa, where 30, 70, 100, 110, and the bands above the size of 250 kDa were observed in the samples. The bands at100 kDa and the bands between 60-75 kDa were the predominant in the samples and they were identified as hyaluronidase. The victims of scorpion bite are suffered from excessive sweating, agitation, tissue destruction at the biting site, and palpitation. Tissue destruction can be occurred due to the action of Phospholipase-A, Neurotransmitter can be a responsible molecule for the palpitation response. The 225kda band and the band between 40-50 kDa would be the responsible bands for acute heart failure in the absence of proper treatment. Therefore, the functional assays should be done in the future to recognize the pharmacological activity of the above novel molecule in action.
Keywords: Scorpionvenom; Protein profile; SDS PAGE; Heterometrus swammerdammi; Black scorpion